Development of an Augmented Reality Concept for Icebreaker Assistance and Convoy Operations - Synne Frydenberg; Katie Aylward; Kjetil Nordby; Jon Olav H. Eikenes (Journal of Marine Science and Engineering, 2021)
A vessel convoy is a complex and high-risk operation completed during icebreaking operations in the Arctic. Icebreaker navigators need to continuously communicate with their crew while monitoring information such as speed, heading, and distance between vessels in the convoy. This paper presents an augmented reality user interface concept, which aims to support navigators by improving oversight and safety during convoy operations. The concept demonstrates how augmented reality can help to realize a situated user interface that adapts to user’s physical and operational contexts. The concept was developed through a human-centered design process and tested through a virtual reality simulator in a usability study involving seven mariners. The results suggest that augmented reality has the potential to improve the safety of convoy operations by integrating distributed information with heads-up access to operation-critical information. However, the user interface concept is still novel, and further work is needed to develop the concept and safely integrate augmented reality into maritime operations.